Implementation of a Mental Health Support Program as an Effort to Improve Adolescent Mental Health - Ramli, Rahmawati; Suhermi, Suhermi; Suyuti, Sartika (Fakultas Ilmu Kesehatan Universitas Borneo Tarakan, 2024)
Teenagers are vulnerable to conditions that can cause pressure (stress). They are faced with various changes that are occurring within themselves as well as development targets that must be achieved according to their age. This challenge certainly has the potential to cause behavioral problems and trigger real stress in teenagers' lives if they are unable to overcome these challenging conditions. The aim of the mental health support program implementation program is to increase adolescent literacy regarding mental health by providing adolescent mental health support programs through communication, information and education activities. The target of this activity is teenagers. The implementation method is by providing counseling through lectures, questions and answers and roleplay about social skills, increasing self-esteem, controlling emotions and managing stress and resolving conflicts. The results of the activity provide an increase in teenagers' knowledge of mental health as measured through pretest and posttest. Suggestions: Mental health support programs can be used as a basis for preventive and promotive efforts on adolescent mental health involving the participation of family, school and peers.Â